Implementasi Pendekatan Transdisciplinary dan Model Inquiry dalam Pembelajaran Social Studies Berbasis International Baccalaureate - Nurrohmatul Amaliyah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2017)
This study describes social learning studies with trandisciplinary approaches and models of inquiry-based learning through strengthening the international baccalaureate curriculum. The theory underlying the birth of this study include the study of the social sciences, learning model, basic education, transdiciplinary and especially international baccalaureate curriculum studies as a scholarly study that is currently being developed as the excellent schools. The method used in this research is qualitative descriptive, which is an approach that seeks to get information from various viewpoints, especially current events, so as to complement the data source to be used as a study that provide significant impact on the development of knowledge, in this case the learning sciences social studies in primary schools in particular. The findings of this research is the implementation of the field approach to transdisciplinary, and a model of inquiry in learning social studies based on the curriculum of international baccalaureate and it is addressed through a review of the comprehensive thus produced that: (1) implementation approach transdiciplinary in social studies based international baccalaureate in class IV Bandung Independent School has been done by teachers whose benefit krikulum still looks too dense; (2) the implementation of social studies learning process by using inquiry-based model of international baccalaureate in Bandung Independent School fourth grade visible is optimal; (3) development process by using pedekatan transdisciplinary learning and social learning model of inquiry in the form of impact studies provide good results in student assessment.